Plant-Derived Nanovesicles from Soaked Rice Water: A Novel and Sustainable Platform for the Delivery of Natural Anti-Oxidant γ-Oryzanol - Jahnavi Ravilla; Soundaram Rajendran; Vidya M. Basavaraj; Greeshma Satheeshan; Janakiraman Narayanan; Thejaswini Venkatesh; Gopinath M. Sundaram (Antioxidants)
Gamma oryzanol (GO) is a natural anti-oxidant found in rice bran with potential health benefits. Conventional isolation of GO from rice bran requires the use of non-eco-friendly solvents such as acetone, ethyl acetate and hexane due to its low aqueous solubility. Further, nanoencapsulation of GO is required for the enhancement of stability and bioavailability. Plant-derived nanovesicles (PDNVs) are natural/intrinsic exosome-mimetic vesicles isolated from edible plants using green methods. Washed/soaked rice water (SRW) is often discarded as waste prior to cooking rice. However, traditional knowledge indicates its health-promoting anti-oxidant benefit, probably contributed by the presence of GO. Herein, for the first time, we isolated PDNVs from SRW by the cost-effective Polyethylene glycol 6000(PEG) precipitation method and demonstrated the presence of GO in PDNVs. In our initial screen, PDNVs were isolated from both rice grains (RGs) as well as the SRW of four different rice varieties, in which we identified the copious presence of GO in black RGs and brown SRW PDNVs. Both RG and SRW PDNVs were non-toxic to keratinocytes. SRW PDNVs displayed distinct cellular uptake mechanisms compared to RG PDNVs in human keratinocytes. Compared to native GO, brown SRW PDNVs containing GO displayed superior anti-oxidant activity in HaCaT keratinocytes, likely due to its enhanced cellular uptake. Overall, we describe here a waste-to-wealth green approach using an economical PEG method for the extraction of GO in bioavailable form. Given that oxidative stress is a driving factor for inflammation and related diseases, SRW PDNVs provide an affordable natural formulation for the treatment of diseases with underlying oxidative stress and inflammation.